Population Synthesis of Black Hole Binaries with Compact Star Companions - Shao, Yong; Li, Xiang-Dong (The Astrophysical journal, 2021)
We perform a systematic study of merging black hole (BH) binaries with compact star (CS) companions, including black hole–white dwarf (BH–WD), black hole–neutron star (BH–NS), and black hole–black hole (BH–BH) systems. Previous studies have shown that mass transfer stability and common envelope evolution can significantly affect the formation of merging BH–CS binaries through isolated binary evolution. With detailed binary evolution simulations, we obtain easy-to-use criteria for the occurrence of the common envelope phase in mass-transferring BH binaries with a nondegenerate donor, and incorporate the criteria into population synthesis calculations. To explore the impact of a possible mass gap between NSs and BHs on the properties of merging BH–CS binary population, we adopt different supernova mechanisms involving the rapid , delayed , and stochastic prescriptions to deal with the compact remnant masses and the natal kicks. Our calculations show that there are ∼10 5 –10 6 BH–CS binaries in the Milky Way, among which dozens are observable by future space-based gravitational wave detectors. We estimate that the local merger rate density of all BH–CS systems is ∼60–200 Gpc −3 yr −1 . While there are no low-mass BHs formed via rapid supernovae, both delayed and stochastic prescriptions predict that ∼100%/∼70%/∼30% of merging BH–WD/BH–NS/BH–BH binaries are likely to have BH components within the mass gap.